Maintaining Maritime Safety Through the Use of Navigational Equipment in Accordance with Solas Chapter V - Anggie Veronica Zuyyana Octavia; Arleiny; Maulidiah Rahmawati; Fazri Hermanto (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Maritime navigation safety remains critical amid rising global and Indonesian shipping incidents, particularly collisions in congested routes, where human error and inconsistent GPS performance in tropical waters contribute significantly to risks despite SOLAS Chapter V mandates for standardized equipment. This study aimed to analyze the implementation and effectiveness of Radar and GPS usage in ensuring safe navigation on the LPG/C Gas Arar vessel during busy Teluk Semangka–Panjang voyages. A qualitative descriptive case study was conducted with purposive sampling of four key deck officers, employing structured observations, semi-structured interviews, and document analysis during sea practice from July 2024 to 2025; data were triangulated and thematically coded using NVivo 14 following Miles et al. (2014). Findings revealed operational Radar and GPS equipment with high SOLAS compliance via SOPs, comprehensive passage plans (Appraisal, Planning, Execution, Monitoring), and effective Bridge Team Meetings, although Radar dominance due to GPS waypoint limitations posed technical risks, mitigated by crew experience and cross-verification. In conclusion, integrated navigation enhances safety but requires GPS optimization; implications include training recommendations to reduce errors by 25–40% in Indonesian LPG fleets